Directions of Internationalization of Kazakhstani Higher Education System - A., Рүстемовa; Ж.Е., Ашиновa; А., Окaдa (Journal of Oriental Studies, 2019)
The process of internationalization in higher education is relatively new, but in a short period of time it has acquired a wide range of concepts and approaches. Internationalization is the process of integrating international and intercultural criteria in the field of educational services, research and training. The main purpose of the article is to identify trends and features of the process of internationalization in higher education institutions of Kazakhstan. The process of internationalization of higher education in Kazakhstan began with the independence of the state and is currently developing dynamically. Based on the qualitative analysis of academic research data, official data of international organizations and website materials, it is argued that the main prospects for the internationalization of higher education institutions in Kazakhstan, including credit mobility, are well developed, however the mobility of teaching staff is still lower compared to students. The unilateral development of academic mobility is also observed. Key words: higher education system of Kazakhstan, the process of internationalization, academic mobility, cross-border education.